Educational interventions that improve the attainment and progress of children in out-of-home car - Sebba, J (Routledge, 2020)
This chapter provides a review of the research evidence on the effectiveness of educational interventions aimed at improving the outcomes of children in out-of-home care (OOHC). The focus is limited to educational interventions during the school years focused specifically on children in OOHC that have educational outcomes. The chapter looks first at systemic interventions involving whole-school approaches before considering the individual interventions targeting children in OOHC specifically and then those interventions targeting their foster carers. Finally, the implications from the evidence reviewed for policy and practice are drawn out. ‘Case study’ illustrations are provided and some discussion questions are provided at the end of the chapter.